Principles of Microeconomics - Taylor, Timothy; Greenlaw, Steven A.; Dodge, Eric; Open Textbook Library (Open Textbook Library, 2014)
Principles of Economics 2e covers the scope and sequence of most introductory economics courses. The text includes many current examples, which are handled in a politically equitable way. The outcome is a balanced approach to the theory and application of economics concepts. The second edition has been thoroughly revised to increase clarity, update data and current event impacts, and incorporate the feedback from many reviewers and adopters. Changes made in Principles of Economics 2e are described in the preface and the transition guide to help instructors transition to the second edition. The first edition of Principles of Economics by OpenStax is available in web view in the ancillaries
Chapter 1: Welcome to Economics! -- Chapter 2: Choice in a World of Scarcity -- Chapter 3: Demand and Supply -- Chapter 4: Labor and Financial Markets -- Chapter 5: Elasticity -- Chapter 6: Consumer Choices -- Chapter 7: Cost and Industry Structure -- Chapter 8: Perfect Competition -- Chapter 9: Monopoly -- Chapter 10: Monopolistic Competition and Oligopoly -- Chapter 11: Monopoly and Antitrust Policy -- Chapter 12: Environmental Protection and Negative Externalities -- Chapter 13: Positive Externalities and Public Goods -- Chapter 14: Poverty and Economic Inequality -- Chapter 15: Issues in Labor Markets: Unions, Discrimination, Immigration -- Chapter 16: Information, Risk, and Insurance -- Chapter 17: Financial Markets -- Chapter 18: Public Economy -- Chapter 19: International Trade -- Chapter 20: Globalization and Protectionism
In English.
Description based on print resource
Keywords: Economics -- Textbooks